Detection Rate and Diagnostic Value of Optical Coherence Tomography Angiography in the Diagnosis of Polypoidal Choroidal Vasculopathy: A Systematic Review and Meta-Analysis - Yuelin Wang; Jingyuan Yang; Bing Li; Mingzhen Yuan; Youxin Chen (Journal of Ophthalmology)
Purpose. This study aimed to evaluate the detection rate of polyps and branching vascular networks (BVNs) in polypoidal choroidal vasculopathy (PCV) by optical coherence tomography angiography (OCTA) and assess the sensitivity and specificity of OCTA in differentiating PCV from wet age-related macular degeneration (wAMD). Materials and Methods. We searched PubMed, EMBASE, Cochrane Library, and other sources. The detection rates of polyps and BVNs in observational studies and the sensitivity and specificity of PCV diagnosis from wAMD in diagnostic studies were extracted. Results. Twenty studies (573 eyes) were eligible. The combined detection rate of OCTA in PCV polyp lesion diagnosis was 0.67 (95% CI: 0.55–0.79), while that of BVNs was 0.86 (95% CI: 0.81–0.91). The detection rate of polyps was compared with that of BVNs in the same study, and the combined relative risk was 0.82 (95% CI: 0.72–0.92). The combined sensitivity of PCV diagnosis in wAMD patients using OCTA was 0.77 (95% CI: 0.55–0.90), combined specificity 0.84 (95% CI: 0.60–0.95), and area under the SROC curve 0.87 (95% CI: 0.84–0.90). Conclusion. OCTA has a high PCV polyp and BVN detection rate, and the detection rate of BVNs is higher than that of the polyp. OCTA has acceptable sensitivity and specificity for diagnosing PCV from wAMD. Thus, OCTA may be helpful for clinical diagnosis of PCV.